Effect of Water Quality on Compressive Strength of Concrete - Ochuko Mary, Ojo (European Scientific Journal, ESJ, 2019)
The effect of water quality on the compressive strength of concrete was evaluated in this study. A total of 100 concrete cubes (150 x 150 x 150 mm) were cast using a mix ratio of 1:2:4. The hardened concrete cubes were de-moulded 24 hours after the cubes were cast and were submerged carefully in a curing tank filled with water. The physico-chemical characteristics of the water used in mixing the concrete was determined according to standard procedures. A slump test was conducted to determine the workability of concrete. Compressive test was carried out on the hardened concrete at 7, 14, 28 days, respectively. Results showed that the physiochemical characteristics of the all the water samples examined fell within acceptable limits set by the World health Organization (WHO) except for the iron, magnesium, and lead contents which were grossly out of acceptable limits. From the slump result obtained, the source of water in mixing concrete doesn’t affect the workability of concrete. The study also revealed that irrespective of the type of water used in making concrete, the development in strength increases with an increase in age.